Jawabanmu

Jawaban paling cerdas!
2014-05-03T22:03:47+07:00
F(x) = 2x(x² - 4)^(-1/3)
f ' (x) = 2(x² - 4)^(-1/3) + 2x(-1/3)(x² - 4)^(-4/3)
f ' (2√2) = 2((2√2)² - 4)^(-1/3) + 2(2√2)(-1/3)((2√2)² - 4)^(-4/3)
             = 2(8 - 4)^(-1/3) + 4√2(-1/3)(8 - 4)^(-4/3)
             = 2(4)^(1/3) - 4√2(2)^(-4/3)
                                   3
             = 2∛4 -   4√2
                           3∛16
             = 6∛64 - 4√2
                    3∛16
             = 24 - 4√2
                   3∛16



1 5 1